Agriculture Student’s Perceptions Toward Native English-Speaking Teachers (NESTs) and Non-Native English-Speaking Teachers (NNESTs) - Fitria Wulandari; Tira Nur Fitria; Adelina Maryanti (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
This study aims to reveal students' perceptions of Native English-Speaking Teachers (NEST) and Non-Native English-Speaking Teachers (NNEST). The study involved students from the Agriculture Faculty of the Riau State Islamic University. This is a quantitative research that employs a survey design. The examination of the data reveals that students had a good assessment of teachers who were either native or non-native speakers. On the other hand, students encountered difficulties when learning with native and non-native professors. Students believe that NEST and NNEST will be more effective if native speakers also study and understand their original language and culture. Instructors who are not natural English speakers should pursue additional education in countries where English is the primary language to hone their abilities. The ideal non-native teachers are those who have reached a level of English proficiency comparable to that of a native speaker. Assuming the talents of the non-native English instructor are optimal, the majority of students believe that as long as instructors display a high level of competence and professionalism, there should be no discrimination between native speakers and non-native English teachers. However, when properly prepared and competent, both native and non-native English teachers can increase the enthusiasm for the student's English skill development. Both have their advantages and disadvantages, and they should collaborate to aid students in becoming successful English learners.